Report of the Group Set Up to Study the Infrastructural Needs of Agricultural Commodities and Processed Foods - Planning Commission (Planning Commission)
Strong prospective markets for Indian flowers do exist in Europe and Japan. The parameters which favour development of export oriented floriculture in the country include availability of wide diversity in natural climate. Abundant labour to the consumer markets on one hand and desire of importing countries to secure material from alternative sources in the context of pricing labour and energy cost in traditional species, sources on the other.
Government of India, Planning Commission